2018
DOI: 10.1002/pits.22102
|View full text |Cite
|
Sign up to set email alerts
|

The effects of traumatic experiences on academic relationships and expectations in justice‐involved children

Abstract: Positive school experiences are an important predictor of long‐term health and well‐being. Developing positive relationships with school personnel and positive academic expectations set the foundation for success. Positive relationships and expectations can be a powerful protective factor or intervention to redirect troubled children toward a more positive path. Unfortunately, children who experience trauma are more prone to academic underachievement and negative school experiences. This link is especially evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…Studies consistently demonstrated the association between ACEs and adverse outcomes for justice-involved youth. In general, the more ACEs youth reported, the higher their risk for mental health and other behavioral concerns including delinquency (Clements-Nolle & Waddington, 2019; Craig, Zettler, et al, 2019; Fox et al, 2015; Johnson, 2018a; Logan-Greene et al, 2017; Perez et al, 2018); this suggests ACEs directly impact youths’ increased likelihood of initial and future juvenile justice involvement. Findings regarding the link between ACEs and substance use were mixed, with one study (Florida dataset) finding ACEs were associated with more substance use (Craig, Zettler, et al, 2019; Perez et al, 2018, 2016; Reid et al, 2019) and two suggesting ACEs were associated with less substance use (Lee & Taxman, 2020; Logan-Greene et al, 2020); of note, the latter studies included youth on probation (Intercept 5), whereas the former included youth across Intercepts 2 through 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies consistently demonstrated the association between ACEs and adverse outcomes for justice-involved youth. In general, the more ACEs youth reported, the higher their risk for mental health and other behavioral concerns including delinquency (Clements-Nolle & Waddington, 2019; Craig, Zettler, et al, 2019; Fox et al, 2015; Johnson, 2018a; Logan-Greene et al, 2017; Perez et al, 2018); this suggests ACEs directly impact youths’ increased likelihood of initial and future juvenile justice involvement. Findings regarding the link between ACEs and substance use were mixed, with one study (Florida dataset) finding ACEs were associated with more substance use (Craig, Zettler, et al, 2019; Perez et al, 2018, 2016; Reid et al, 2019) and two suggesting ACEs were associated with less substance use (Lee & Taxman, 2020; Logan-Greene et al, 2020); of note, the latter studies included youth on probation (Intercept 5), whereas the former included youth across Intercepts 2 through 5.…”
Section: Discussionmentioning
confidence: 99%
“…Other outcomes. Three articles (67% longitudinal) examined the impact of ACEs on other outcomes, including academic (n=2; Johnson, 2018a;Perez et al, 2016) and victimization (n=1; Reid, Baglivio, Piquero, Greenwald, & Epps, 2017). Sample size (range=2,558-68,218), gender representation (% female range=18-24), and number of ACEs assessed (range=9-10; 67% assessed 10) varied.…”
Section: Substance Use Outcomesmentioning
confidence: 99%
“…Trauma experiences (e.g., accidents, natural disasters, sexual/physical abuse as a child or adult, military service; Carlson et al, ) have been associated with both positive and adverse reactions in clients (Tedeschi & Calhoun, ). Adverse trauma reactions include feelings of loss of control (Dekel et al, ), increased drug and alcohol use (Read et al, ), academic underachievement (M. E. Johnson, ), and depressive symptoms (Gallus et al, ). Furthermore, chronic exposure to complex trauma can increases a person's likelihood of developing psychological distress consistent with symptoms of posttraumatic stress disorder (PTSD; Scott, ).…”
mentioning
confidence: 99%
“…Está bem estabelecido na literatura que dentro do microssistema familiar podem ser encontradas diversas situações potencialmente dificultadoras do aprendizado das crianças (JOHNSON, 2018;TZOUMAKIS et al, 2018). Como, por exemplo, a baixa escolaridade dos pais, em especial, a materna (BRAVO et al, 2017;STRAND, 2014;WINSLER et al, 2012).…”
Section: Dificuldades Ou Transtornos De Aprendizagem? Breve Diferenciação Dos Termosunclassified
“…Na esfera familiar, os fatores de risco mais citados estão ligados a estrutura e a dinâmica familiar, tais como: (a) ser filho/a de mãe menor de vinte anos de idade; (b) pertencer a um grupo familiar com membros com histórico de abuso de substância ilícitas e/ou antecedentes criminais; (c) ter sofrido exposição pré-natal pesada ao álcool e/ou tabaco antes, durante e/ou após a gestação; (d) pertencer a família monoparental; (e) pertencer a um grupo familiar formado majoritariamente por membros do sexo feminino e residir em uma casa com três ou mais crianças menores de cinco anos; (f) ter ingressado tardiamente na escola e ter tido uma preparação deficitária para ingressar na pré-escola. Em seguida, ainda na categoria "fatores de risco ligados à família", aparecem reiteradamente os seguintes fatores: (g) baixo nível socioeconômico; (h) baixa escolaridade dos pais e (i) maus tratos na infância; (j) pais com problemas de saúde mental e (k) violência doméstica (BRAVO et al, 2017;BUSSING et al, 2012;CALZADA et al, 2015;COMPTON et al, 2012;DHAVAN et al, 2010;DUNN et al, 2010; ENRIQUEZ GUERRERO; CATAÑO ORDONEZ, 2009; ENRIQUEZ GUERRERO; SEGURA CARDONA; TOVAR CUEVAS, 2013;FANTUZZO et al, 2012;GUERRERO et al, 2013;JOHNSON, 2018;NIEMI et al, 2011;O'LEARY et al, 2013;SANDERS;FALLON, 2018;STERGIAKOULI et al, 2017;STRAND, 2014;TZOUMAKIS et al, 2018;VIEIRA et al, 2012;WINSLER et al, 2012;ZUANETTI;FUKUDA, 2012). prematuro ou abaixo do peso.…”
Section: )unclassified